THE INFLUENCE OF PRODUCT VARIATIONS ON PURCHASING DECISIONS WITH CELEBRITY ENDORSER AS A MODERATING VARIABLE - Kalalo, Rieneke Ryke; Amri, Andi; Tawil, Muhammad Risal; Suseno, Bambang; Akhmad, Noor (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This research is a quantitative study with an explanatory approach. The data used are primary data that researchers obtained from users of shopee, tikthok shop, and facebook marketplaces spread throughout Indonesia. The data was collected in the form of a questionnaire from 24 questions from 300 users of shopee, tiktokshop, and the Facebook marketplace mentioned above. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show shows that the first and second hypotheses used in this article can be proven and accepted. This is because the P-Values are positive and below the significance level of 0.05, namely 0.021. This is because the more product variations make buyers more interested in making purchasing decisions, the less easily bored, and so on which make purchasing decisions even greater. In the next row, the results answer the second hypothesis where the Celebrity Endorser variable can strengthen the influence of the Product Variation variable on Purchasing Decisions. This is because the same thing is the P-Values that are positive and below the significance level of 0.05, which is 0.000, which is smaller than direct testing of 0.021. Thus it can be concluded that the first and second hypotheses in this article can be accepted and proven. Keywords: Fear of Missing Out, Price Perception, Social Media Promotions, Consumer Satisfaction and Purchase Decision